FACTORS AFFECTING CONSENSUS OF LOCAL PEOPLE IN NEW RURAL DEVELOPMENT PLANNING PROGRAM: A CASE STUDY OF HOANG VAN THU COMMUNE, CHUONG MY DISTRICT, HANOI - Thu Ha, Tran; Thi Huong, Do; Thanh Que, Pham; Van Hoa, hO; Minh Tam, Phung (Journal of Forestry Science and Technology, 2020)
The national target program on new rural development has been widely implemented in many rural areas in Vietnam since 2010. This program was expected to improve the economy and the living standards of Vietnam's rural people. This study aimed to investigate levels of local people's consensus and its affecting factors in new rural development planning in Hoang Van Thu commune, Chuong My district, Hanoi. 190 structured - interviews were conducted in 7 villages of Hoang Van Thu commune. Exploratory factor analysis and multiple regression analysis methods were mainly applied to identify and verify the consensus of local people and factors affecting the local people's consensus in new rural development planning in the study area. Our results showed that local people's consensus was relatively high and was determined by four factors, including Transparency, Understanding, Supervision, and Contribution, with coefficient β of 0.378, 0.373, 0.364, 0.235, respectively. This study also revealed that there was not a close relationship between the capacity of government and the consensus of the local people. Based on the results, it is suggested that a focus should be put into strengthening the involvement of local people in discussion, consultation, monitoring, and supervision in the implementation of new rural development planning.